Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/19338244.2013.853645
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Respiratory and Dermal Symptoms Among Ethiopian Flower Farm Workers

Abstract: The flower industry is among the most important export industries in Ethiopia, employing more than 50,000 workers. The working conditions and health status among workers in Ethiopian flower industry are not documented. A questionnaire-based interview was conducted among 213 flower industry workers from 3 flower farms and 60 control workers from supermarkets from February to March 2012. A walk-through survey was also performed on the 3 flower farms. Interviewed flower farm workers have high prevalences of respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 61 publications
4
40
1
Order By: Relevance
“…Data from our study showed that respiratory ailments are common among workers at farms growing rambutan, durian, longan, and long kong. Overall, 55% of the migrant farm workers developed cough symptoms, 56.2% had phlegm, and 46% had dyspnea, consistent with an earlier study by Hanssen et al [46], which focused on the prevalence of chronic cough symptoms in Ethiopian farm workers (43.7%). The overall difficulty in breathing (70.2%) corresponded to the findings of a study conducted on workers in vineyards and mango farms, which reported several respiratory disorders, including dyspnea and suffocation crisis (74.1% vs. 5.2%), cough (27.6% vs. 15.7%), expectoration (25.3% vs. 13.8%), and chronic bronchitis (20.7% vs. 13.9%) [47].…”
Section: A Factors Related To Respiratory System Distress Symptomssupporting
confidence: 88%
“…Data from our study showed that respiratory ailments are common among workers at farms growing rambutan, durian, longan, and long kong. Overall, 55% of the migrant farm workers developed cough symptoms, 56.2% had phlegm, and 46% had dyspnea, consistent with an earlier study by Hanssen et al [46], which focused on the prevalence of chronic cough symptoms in Ethiopian farm workers (43.7%). The overall difficulty in breathing (70.2%) corresponded to the findings of a study conducted on workers in vineyards and mango farms, which reported several respiratory disorders, including dyspnea and suffocation crisis (74.1% vs. 5.2%), cough (27.6% vs. 15.7%), expectoration (25.3% vs. 13.8%), and chronic bronchitis (20.7% vs. 13.9%) [47].…”
Section: A Factors Related To Respiratory System Distress Symptomssupporting
confidence: 88%
“…Hanssen et al 18 reported prevalences of 43.7% and 70.2% for chronic cough and shortness of breath among farm workers in Ethiopia. These prevalences were more similar to the prevalences observed in the second survey, possibly suggesting that disease reporting was more complete in the second survey.…”
Section: Discussionmentioning
confidence: 99%
“…Though Ethiopia has endorsed a labour proclamation in order to minimise and control risks in occupational settings,16 previous studies have shown higher prevalences of respiratory symptoms17 18 and reductions in respiratory function19 20 in individuals occupationally exposed to pesticides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative health effects of pesticides vary from short-term (skin irritation, eye irritation, headache, dizziness and nausea) to chronic health impacts (asthma, diabetes and cancer) [10]. Numerous pesticides are used on flower farms and represent different chemical and hazard classes, some of them belonging to the hazard class I and II according to the classification of the World Health Organization (WHO) [11][12][13]. According to the Ethiopian Ministry of Agriculture, around 300 chemicals are used by the flower industry in Ethiopia [14].…”
Section: Introductionmentioning
confidence: 99%